Analisis Peningkatan Produk Laptop Melalui Brand Attitude Dan Brand Credibility - Fauzie Senoaji; Hendy Tannady; Ika Suhartanti Darmo; Sutrisno Sutrisno; Nia Sonani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research to understand the effect of brand credibility and brand attitude towards the buying interest of Huawei laptop. The data on this research is using purposive sampling method with the criteria that knows about Huawei laptop and at least 17 years old. The result of this hipotesis test shows that brand credibility variable has effect to buying interest with significant score of 0,028 < 0,050, brand attitude variable has effect to buying interest with significant score of 0,00 < 0,050, and also the brand credibility and brand attitude variable simultaneously effect the buying decision with fscore > ftabel with 124,209> 2,682.